1977
DOI: 10.1161/01.res.41.2.256
|View full text |Cite
|
Sign up to set email alerts
|

The effect of norepinephrine on aortic 42K turnover during deoxycorticosterone acetate hypertension and antihypertensive therapy in the rat.

Abstract: We studied the effects of norepinephrine on 42K turnover in aorta isolated from rats. The rats were given saline to drink and were made hypertensive by injections of deoxycorticosterone acetate (DOC). Other groups of rats received in addition either 6-hydroxydopamine (6-OH-DA) or a regimen of antihypertensives (Anti-Hy) consisting of reserpine, hydrochlorothiazide, and hydralazine. The weight, length, wall thickness, and circumference of the aorta also were measured. DOC hypertension was associated with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Histological examination of tissue slices from kidneys denervated in this manner showed that there was no catecholamine fluorescence at 6 weeks postdenervation. It has also been shown that an intact sympathetic nervous system was not a requirement for the development of an increased responsiveness to NE or an increased potassium turnover in aortae from DOCA hypertensive rats (Jones et al, 1977).…”
Section: Peripheral Sympathectomymentioning
confidence: 99%
“…Histological examination of tissue slices from kidneys denervated in this manner showed that there was no catecholamine fluorescence at 6 weeks postdenervation. It has also been shown that an intact sympathetic nervous system was not a requirement for the development of an increased responsiveness to NE or an increased potassium turnover in aortae from DOCA hypertensive rats (Jones et al, 1977).…”
Section: Peripheral Sympathectomymentioning
confidence: 99%
“…The response to a given dose of NE, Ak, was taken as the difference between the highest rate constant in the presence of the agonist and the rate constant for the wash period just before exposure to NE. The maximal response, Ak,,,, was taken as the response to a supramaximal dose of NE, 6 X 1 O-' M (9). The individual responses, Ak, were normalized in terms of Akmax for each aorta and represented as percentage.…”
Section: Methods Animal and Tissue Preparationmentioning
confidence: 99%
“…Increased blood and plasma volume (3), elevated levels of an adrenal mineralocorticoid, 1 80H-DOC (4), and hyperresponsiveness to intravenous injection of various pressor agents (5-7) have been reported in the hypertensive S rat when compared to normotensive controls. In models of hypertension induced by mineralocorticoid plus salt (8)(9)(10) as well as the SHR (spontaneously hypertensive rat) form of genetic hypertension ( 1 I), norepinephrine supersensitivity has been associated with altered ionic transport in vascular smooth muscle. It is feasible, then, that the vascular smooth muscle of the genetically salt-sensitive Dahl S rat may exhibit similar ionic transport alterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Membrane supersensitivity to norepinephrine (NE) also occurs during mineralocorticoid hypertension in rats as measured by agonist-induced increases in 42 K efflux. 9 l0 This supersensitivity may extend to several types of agonists including peptides and indicates that a relatively nonspecific supersensitivity develops." It is not clear whether the development of drug supersensitivity is closely related to the alteration in resting fluxes, or whether it results from altered receptor syn-thesis, control, and transduction with membrane channels.…”
mentioning
confidence: 99%